PENGARUH PEMBERIAN PENDIDIKAN KESEHATAN MOBILISASI DINI DENGAN LAMA HARI RAWAT PADA PASIEN POST OPERASI SECTIO CAESARIA - Mariati, Mariati (JURNAL MEDIA KESEHATAN, 2015)
Sectio Caesaria (SC) is a surgery to birth a child through an incision in theabdomen wall and uterus. The incidence of SC in Indonesia according to National SurveyData on 2007 is 22,8%. The labor case of SC in M.Yunus Hospital Bengkulu on 2011 is51,51%. 48,61% on 2012 and 47,84% on 2013. Childbirth by SC is not save alternativebecause it need special supervision of indication for SC. It need intensive monitoring untilmother indicated healthy, one of effort is Early ambulation as a wisdom for guiding patientsto get out from their bed until they can ambulation. Aim of research is known comparison ofadministration health education of early mobilitation to the patient with post operation of SCwith long day care in the hospital of Bengkulu City. Kind of research is Quasi Experiment fordetermine whether ther is a causal effect between indedendent variable and dependent variablewith compare one or more experiment groups fed with the comparison groups. Sample takenConsecutive Sampling. Population is mother of labor in intervention groups as much as 21respondents and 21 respondent for control groups. Bivariate analysis of median long day careto the mother group that administration health education of early mobilitation to the motherpost operation section caesaria as much as 3.00 with minimum value of long day care was 2and maximum value was 6.00 and average and standard deviation was 0,20. Result of MannWhitney Statistic Test showed that p=0,00 value means there was significant correlationadministration education of mobilitation to the long day care to the mother with post operationof section caesaria. Result of Multivariate Analysis together between health education ofearly mobilitation and age with long day care, it showed that p=0,00 value means there wassignificant correlation between health education of early mobilitation and age with long daycare. By controlling variable of age could prediction long day care as much as 51%.Health education of early mobilitation to the intervention groups showed that average of longday care faster than control groups. There was significant correlation between healtheducation of early mobilitation to the long day care for patient post operation section caesaria.